The social ideal as a component of the trans historicity mythological consciousness - Полисаєв, О.П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
Considered a myth, both traditional and modern, which "controls" the reality of the real world of human existence and society from the standpoint of the ideal - a universal cosmic order. Ideas and concepts about the prospects of the individual and society get the ideal status only if the entry directly social character, and any ideal, functioning in society, the public, regardless of the imaged object in various forms of human activity, integrating a aesthetic , moral, religious, scientific and other aspects of reproduction in the public consciousness.